Analysis of Regulatory Parameters of Fuel Consumption by Gasoline Engines (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
All known automotive concerns and institutes specialized in ICE problems have worked to identify the relationship between the compression ratio of ICE and its efficiency and to investigate the nature of thermodynamic processes taking place in ICE.Numerous experiments have also been carried out to increase the compression ratio of ICE. But these works had a negative result. Building on this negative result, ICE theory adopted, as axioms, claims that the compression ratio of a gasoline engine cannot be higher than 14. That the most effective compression ratio of the diesel internal combustion engine is in the region 17-23, and at the compression ratio 40 it becomes zero. Experts and theorists were so established in the correctness of these provisions that at this stage the slightest attempt to question them caused a sharp reaction.